Cenários, olhares, tramas e cotidiano [manuscrito]: a educação ambiental à luz de distintas representações e territorialidades na Ilha do Bananal e entorno - TO - BISPO, Marcileia Oliveira (2012)
The environmental education is an educational practical developed in the formal education of environmental dimension in the daily social. We observe nowadays the multiplicity of resources what goes get to constitute, a new way to produce knowledge a new way to think about the reality. Therefore, the present study emphasize the representations, built for determined groups and that can contribute for a practice of a environmental education in the public schools. The place chosen for development of resource was Bananal Island and outskirts TO, specially in the city hall Pium, Cristalândia, Confusion Lake and Formoso do Araguaia. The main objective of the study was to analize as the guys which live in the Bananal Island and outskirts TO relate with this place and construct territorialities, aiming to understand the representations constructe by colaboraters of investigation about Bananal Island and that forms this knowledge can contribute for the practice he environmental education in the public schools of outskirts of Island. Some objectives was established taking as reference the observation of reality to understand the relations of communities of outskirts of Bananal Island and the livers and managers of PARNA do Araguaia, from yours representations about own Bananal Island, such as: to identify the territorialities constructed by the subjects what live in the Bananal Island and outskirts; to identify the conflicts from the different types or uses and the territorialities of subjects of resource; to investigate in the public schools of cities resource development the Environmental Education determining as its happen and if the practice of EE related with the conflicts of resource region, and finally to suggest strategies de EE for teachers with base in the knowledge of territorialities and the conflicts in the Bananal Island and outskirts TO. By the bibliography resource, documental analyses, observations and the field resource and utilizing the interview and the personal opinion, we develop a resource of a quality nature. From the answers of the subjects of resource teachers, farmers withdrawers, Indians and managers of National Park of Araguaia, showed the territorialities and the territories formation, identifiers, what identify relation territory has in the place the sense of belonging of guys that live and conceive his, and still this feeling of belonging express several forms. We observe still that conflicts of use of territory of Bananal Island for this subject as well one diversity of representations this territory, staying obvious what from like this perceive and represent of Bananal Island, orient to look each one, each one inside of his specificities, and when the representations are assimilated express the relation of guy with the world and same time place the guy in this world. Finally, the information introduced a vision as well the practice at environmental education in the area resource. Was possible give some suggests of intervention, because all proliferating of actions in the schools had as of environmental education we perceive that same continues in character sensitive and innocent that only the change of behavior is enough to resolve the environmental problems.